EFFICACY OF AN HERBAL FORMULATION FOR WOUND HEALING MANAGEMENT IN CATTLE - Mohammed, S Peer; Sundaramari, M; Punniamurthy , N; Ramanathan , A (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The results of the present study indicated that the herbal ointment enhanced healing of septic wounds in cattle. This prohealing effect is comparable to that of commercial povidone ointment and could be attributed to tissue proliferating and antibacterial activity of the constituent herbs. The herbal ointment was found to be cost effective since it is prepared from locally available herbs with indigenous techniques.